1998
DOI: 10.1103/physreve.58.3168
|View full text |Cite
|
Sign up to set email alerts
|

Boundary limitation of wave numbers in Taylor-vortex flow

Abstract: We report experimental results for a boundary-mediated wavenumber-adjustment mechanism and for a boundary-limited wavenumber-band of Taylor-vortex flow (TVF). The system consists of fluid contained between two concentric cylinders with the inner one rotating at an angular frequency Ω. As observed previously, the Eckhaus instability (a bulk instability) is observed and limits the stable wavenumber band when the system is terminated axially by two rigid, non-rotating plates. The band width is then of order ǫ 1/2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…J.A .Cole [7] has found that the Taylor number for the onset of wavy vortex flow increases considerably as the annulus height is reduced. M. Linek et al [8] have presented experimental results, which demonstrate that Taylor-system terminated at one end by a liquid-air interface has a band of solutions, which is narrower than the Eckhaus-stable band of the system with rigid nonrotating ends. A. Mahamdia et al [9,10] have found that the appearance of Taylor vortices does not depend on the fluid height and the appearance of wavy mode is delayed when the aspect ratio decreases .…”
Section: Introductionmentioning
confidence: 99%
“…J.A .Cole [7] has found that the Taylor number for the onset of wavy vortex flow increases considerably as the annulus height is reduced. M. Linek et al [8] have presented experimental results, which demonstrate that Taylor-system terminated at one end by a liquid-air interface has a band of solutions, which is narrower than the Eckhaus-stable band of the system with rigid nonrotating ends. A. Mahamdia et al [9,10] have found that the appearance of Taylor vortices does not depend on the fluid height and the appearance of wavy mode is delayed when the aspect ratio decreases .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the flow behavior in the short cylinders has been the subject of numerous theoretical, experimental and numerical studies (Hall, (1982); Lücke et al, (1984); Aitta et al, (1985); Heinrichs et al,(1986); Pfister et al, (1988); Nakamura et al,(1990Nakamura et al,( , 1989; Cliffe et al, (1992); Toya et al, (1994); Linek and Ahlers, (1998); Mullin et al, (2002); Czarny et al, (2002); Furusawa et al, (2002); , Lopez and Marques, (2003); Watanabe and Toya, 2012)). Recently, Deng et al, (2009) presented an experimental and numerical study on the onset of Taylor vortices in short cylinders with an aspect ratio of 5.17.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly in the symmetric system with both stationary end walls [14], Nakamura et al [15] and Toya et al [16] found normal, secondary and anomalous flow mods in the asymmetric system and carried out a systematic research to investigate the transition processes during the quasi-steady decrease of the Reynolds number. Linek et al [17] studied the developing processes of the asymmetric system. Following these studies, Watanabe et al [18] numerically investigated the asymmetric system at very small aspect ratio (ratio of the cylinder length to the gap width between two cylinders) below 4.2, and found a reasonable coincidence with the experimental results.…”
Section: Introductionmentioning
confidence: 99%